Mitochondrial Quality Control in Hepatocellular Carcinoma - Bian, Jinda; Zhang, Dan; Wang, Yicun; Qin, Hanjiao; Yang, Wei; Cui, Ranji; Sheng, Jiyao (Frontiers in Oncology, 2021)
Mitochondria participate in the progression of hepatocellular carcinoma(HCC) by modifying the redox homeostasis, metabolism, and cell death pathway, and so on. These processes depend on the mitochondrial health status. Mitochondrial quality control can repair or eliminate “unhealthy mitochondria” at the molecular, organellar, or cellular level and form an efficient integrated network and play important roles in tumorigenesis, survival, and progression in HCC. Here, we first review the influence of mitochondria on the biological behavior of HCC. On this basis, we further highlights the need for elucidating the role and mechanism of interaction between different levels of mitochondrial quality control for regulation of the occurrence, progression, and resistance in HCC. We hope to provide an opportunity to develop precision medicine against select candidates involved in different mitochondrial quality control-related pathways.